Design of low power 8-bit gate-diffusion input (GDI) full adder using variable body bias (VBB) technique in 90nm technology - Woo Wei Kai; Nabihah Ahmad; Mohamad Hairol Jabbar (Institute of Advanced Engineering and Science, 2019)
In digital system, the full adders are fundamental circuits that are used for arithmetic operations. Adder operation can be used to implement and perform calculation of the multipliers, subtraction, comparators, and address operation in an Arithmetic Logic Unit (ALU). The subthreshold leakage current increasing as proportional with the scaling down of oxide thickness and transistor in short channel sizes. In this paper, a Gate-diffusion Input (GDI) circuit design technique allow minimization the number of transistor while maintaining low complexity of logic design and low power realization of Variable Body Biasing (VBB) technique to reduce the static power consumption. The Silterra 90nm process design kit (PDK) was used to design 8-bit full adder with VBB technique in full custom methodology by using Synopsys Electronic Design Automation (EDA) tools. The simulation of 8-bit full adder was compared within a conventional bias technique and VBB technique with operating voltage of supply. The result showed the reduction of VBB technique in term of peak power, and average power, compare with conventional bias technique. Moreover, the Power Delay Product (PDP) showed 1.29pJ in VBB technique compare with conventional bias mode 1.67pJ. The area size of 8-Bit full adder was 10μm×23μm.